Innovation Decision Efficiency on Selected Fishing Technologies among the Steel Fishing Trawler Operators - Jeeva, J Charles; Vasanthakumar, J; Balasubramaniam, S; Ashaletha, S (Fishery Technology, 2025)
The innovation decision process was conceptualized as the process in which a mechanized steel fishing boat operator passes through knowledge, persuasion, decision, implementation and confirmation stages in adopting selected fishing technologies identified for the study. The overall innovation decision efficiency index was 79%. The indices on passing through the five stages of innovation decision process viz., knowledge, persuasion, decision, implementation and confirmation were 96, 82, 72, 72 and 72 percentages respectively. The results revealed that 100% of the clientele reaching the decision stage were passing through the implementation and confirmation stages, establishing that passing from persuasion to decision stage was very crucial in the innovation decision process. The RÂ² was 0.71, indicating that seventeen socio-personal variables selected accounted for 71% of variations in the innovation decision efficiency level. Six socio-personal characteristics such as educational status, investment on fishing craft and gear, innovativeness, extension participation, communication behaviour and extent of linkage with research and extension groups acted as crucial factors in determining the efficiency of innovation decision behaviour of the steel fishing trawler operators. The constraints in the innovation decision process pertaining to the identified technologies were also presented.